Expect the worst, hope for the best: The valuation of climate risks and opportunities in sovereign bonds - Julia Anna Bingler (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
How climate aspects affect sovereign bonds is still a new field of research. I differentiate between transition, physical, and innovation aspects of climate risks and climate performance and estimate the pricing-in of these climate aspects in sovereign bond yields for a sample of 29 countries, for the time 2008-2021. The results show that the effects differ between countries with higher and lower credit rating, long- and short term maturities, and the periods of analysis. Financial markets seem to expect the worst with regards to physical risk exposure and impacts, which are associated with higher yields for the lower-rated countries' bonds at longer-term maturities. In contrast, they seem to hope for the best with regards to transition risk exposure and innovation opportunities, which are associated with lower bond yields for the countries with higher credit rating, mainly for bonds at shorter-term maturity. The effects are more pronounced for the period after the Paris Agreement and might gain increasing importance as physical and transition risks aggravate in the future.
Keywords: G12; G14; Q54; Q55; 330; sovereign bonds yields; climate physical risks; climate transitionrisks; climate opportunities; LASSO dimensionality reduction